The Relationship between Teachers' Qualification, Availability of Relevant Equipment and Students' Performance in School Certificate Biology - Ogunleye, Adedokun M. (Obafemi Awolowo University, 2014)
This study investigated the relationship between qualifications, availability of relevant equipment and performance in West African School Certificate (WASC) Biology (1979). Three types of questionnaire were used (a) qualifications questionnaire (XQ), (b) availability of relevant equipment questionnaire (YEQ) and (c) School Certificate Biology result for I979 questionnaire (ZR). The YR ,and XQ questionnaires were used to collect information from relevant schools and the west African Council's (WAEC) records.